2021
DOI: 10.1016/j.psj.2021.101096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytosterol supplementation on growth performance, serum lipid, proinflammatory cytokines, intestinal morphology, and meat quality of white feather broilers

Abstract: The aim of this study was to evaluate the effects of dietary phytosterol ( PS ) addition at different levels on growth performance, serum lipid, proinflammatory cytokines, intestinal morphology, and meat quality in broilers. A total of 600, 1-day-old male broilers were allocated into five groups with six replicates and were fed a basal diet supplemented with 0 (control group), 10, 20, 40, or 80 mg/kg PS for 42 days. Compared with the control group, the administration of PS at doses of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…This result was consistent with an earlier finding of Cheng et al (2019) . The improved feed utilization efficiency resulting from BS administration observed in this study could be explained by the increased nutrient digestibility, elevated pancreatic and small intestinal digestive enzyme activities, improved antioxidant capacity and immune function, and the better intestinal morphology, as reported previously ( Hu et al, 2017a , b ; Cheng et al, 2019 , 2020 ; Zhao et al, 2019 ; Ding et al, 2021 ; Yuan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This result was consistent with an earlier finding of Cheng et al (2019) . The improved feed utilization efficiency resulting from BS administration observed in this study could be explained by the increased nutrient digestibility, elevated pancreatic and small intestinal digestive enzyme activities, improved antioxidant capacity and immune function, and the better intestinal morphology, as reported previously ( Hu et al, 2017a , b ; Cheng et al, 2019 , 2020 ; Zhao et al, 2019 ; Ding et al, 2021 ; Yuan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…Up to date, multiple studies have investigated the consequences of dietary administration with different levels of phytosterol on growth performance of different animal species including poultry ( Zhao et al, 2019 ; Ding et al, 2021 ; Yuan et al, 2021 ), swine ( Hu et al, 2017a , b ), and aquatic animals ( Couto et al, 2014 ; He et al, 2022 ), but the used phytosterol in these studies is almost a kind of phytosterol mixture varying in compositions, rather than a single phytosterol source. As for broilers, Ding et al (2021) have reported that the administration of phytosterol at the doses of 40 and 80 mg/kg significantly increased feed intake and weight gain in white-feathered broilers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations